Linking teaching and research in disciplines and departments - Jenkins, Alan; Healey, Mick; Zetter, Roger (Higher Education Academy (HEA), 2007)
This volume is aimed at discipline-based staff who wish to connect their teaching and research roles; those with leadership roles for teaching and for research in departments and intuitions, and for educational developers. The central arguments in the book are that: the 'teaching-research nexus' is central to higher education student intellectual development and staff identity can and should be developed by departments focusing on the 'nexus' effective teaching-research links are not automatic and have to be constructed there are important disciplinary variations in teaching-research relations that need to be valued academic departments are central to developing the links between research in the discipline and student learning a central way to develop effective practice is to share case studies of discipline-based practice and department policies. Suggestions are offered as to how disciplinary communities and departments can strengthen the good practice that already exists